Safe-Testing Algorithm for Individual-Donation Nucleic Acid Testing: 10 Years of Experience in a Low-Prevalence Country - Stolz, Martin; Gowland, Peter; Tinguely, Caroline; Niederhauser, Christoph (Transfusion medicine and hemotherapy, 2019)
A highly sensitive and specific nucleic acid test (NAT) for the blood-borne viruses human immunodeficiency virus (HIV), hepatitis C (HCV), and hepatitis B (HBV) is essential for the safety of blood components. Since more than 2 decades, NAT screening of blood donations has become standard in developed countries that have implemented the individual-donation (ID-NAT) and mini-pool NAT (MP-NAT) approaches. With this powerful technique, confirmation of initial reactive (IR) NAT samples becomes a challenge. Different algorithms are currently in use to eliminate false reactive results. To show that the algorithm implemented in 2007, that uses repeat testing of IR samples in duplicate runs, is a safe strategy, especially in low endemic countries, data from a 10-year experience of ID-NAT were extensively analyzed when follow-up data were available. From July 2007 to December 2014, the Procleix Ultrio assay on a Procleix Tigris system, and from January 2015 to December 2017, the cobas MPX on a cobas 8800 platform, were used for ID-NAT screening. All IR samples were subjected to repeat testing in duplicate independent runs. Only when both tests remained negative were the products released. Donor data from the last 10 years were investigated retrospectively, looking for the reoccurrence of a reactive result in a follow-up sample. Only those donors with at least an x + 1 donation result were included for the confirmation of a false reactive result. From the 1,830,657 donations tested, 2,450 samples were IR (0.13%); only 228 were repeat reactive ([RR], 18 HIV, 61 HCV, and 149 HBV samples), and 2,222 were non-RR (0.12%). Follow-up data were available from 1,267 donors (57%) for further analysis. All except one of these donors were ID-NAT-negative in all follow-up samples. The one exception was from a donor who acquired a fresh HBV infection 10 years after the IR donation (in the x + 28 donation) and subsequently seroconverted. Subsequent serological tests from all succeeding donations (x + 1, x + 2, etc.) were negative in all the other cases, proving that no seroconversion took place after the IR ID-NAT result. The algorithm to deal with IR ID-NAT donations using duplicate repeat testing is very safe and cost-effective in low-prevalence countries. There is no unnecessary destruction of blood products, no counseling of false reactive donors, and also no need to add further complexity to the screening algorithm.